Energy-Saving Intelligent Models Of Energy Facility Control Systems (Using The Example Of “Energy Facilities”) - Bakhrieva X.A.; Jaksimov D.B. (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
This paper is devoted to the development of an energy-saving intelligent control model for power facilities. Classic power engineering systems, including turbogenerators, boilers, pumps, and distribution grids, are considered. A specific mathematical model for optimal control of turbogenerator operating modes is proposed using intelligent predictive control and a trainable fuel consumption model. The model enables energy loss reduction. The results of a comparative analysis of a traditional PID controller and the developed intelligent model predictive control (IMPC) are presented. Evaluation was conducted using four key metrics: average control error, fuel savings, power loss reduction, and system response time. Experimental data obtained under conditions simulating the operation of a 200 MW turbine control circuit of a power facility were used for the analysis. This model aims to minimize fuel consumption and ensure accurate load schedule compliance. The article describes in detail the structure of the proposed model, its mathematical model, optimization algorithm, and practical significance. An analysis of the model's capabilities was conducted, and it was shown that its implementation allows for a reduction in fuel costs by 5–9%, a reduction in power losses in the network by up to 12%, and a reduction in deviations from the load schedule by 4 times compared to traditional PID control.